Amplified Sensitivity in SERS Detection of L1CAM With Silver Plasmonic Mesoporous Silica Capsules on an Imprinted Films - Yuselis Castaño‐Guerrero; Belén Arjones‐Fernández; Felismina T.C. Moreira; Ramon A. Alvarez‐Puebla; Miguel A. Correa‐Duarte; H. Águas; M. Goreti F. Sales (Advanced Materials Interfaces)
Abstract This study presents a novel approach for dual detection, leveraging a combination of a Raman reporter‐bearing nanomaterial and molecular imprinting polymers (MIP). A core‐shell Au‐Ag nanoparticles (Au‐Ag NPs) encapsulated in mesoporous silica nanocapsules (Au‐Ag NCs) and a new MIP‐based material targeting L1CAM are used. The MIP prepared via surface imprinting on a carbon screen‐printed electrode (C‐SPE) used thionine (TH) as a monomer. The plasmonic Au‐AgNCs are further functionalized with the Raman reporter 4‐mercaptobenzoic acid (MBA) and anti‐L1CAM for selective detection by surface‐enhanced Raman scattering (SERS) spectroscopy. The biosensor's analytical performance is evaluated using both SERS and electrochemical impedance spectroscopy (EIS). EIS analysis reveals a linear response within the concentration range of 0.1 to 100 ng mL−1 in buffer and serum samples. SERS demonstrates a sensitivity ten times higher than EIS. Selectivity study demonstrates the biosensor's excellent specificity toward L1CAM, with minimal interference from other compounds such as creatinine, glucose, and carbohydrate antigen 19‐9 (CA 19‐9). The Raman signal from the reporter molecule correlates with increasing L1CAM concentrations, reinforcing the analytical findings obtained through electrochemical analysis. Thus, the combination of dual detection and recognition capabilities presents promising potential for detecting diverse biomarkers, especially in critical scenarios where reducing false‐positive or false‐negative errors is crucial.